The comparison of the responses of bone marrow and peripheral stem cell products from patients with non-Hodgkin lymphoma to interleukin-2 (Annals of Medical Research, 2021)
None
Keywords: s : Non-Hodgkin lymphoma, IL-2, bone marrow cell, peripheral stem cell